DEHUMANISASI KEGIATAN BELAJAR MENGAJAR MATA PELAJARAN IPS SEMESTER II PADA MTs. AL-AZHAR TUWEL KECAMATAN BOJONG KABUPATEN TEGAL - Nafiati, Dewi Amaliah (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The objective of the study is to describe the factors which influence the dehumanization on the teaching learning process at 8th grade students in MTs. Al-Azhar Tuwel. The population of this study were 158 students which were all 8th graders in MTs. Al-Azhar Tuwel in the academic year of 2014/2015. It used proportional cluster random sampling for 25%, or there were 40 students as the samples. The data were collected by documentation, observation and questionnaire with Guttmant scale. Then, the data were classified by two techniques; quantitative and qualitative data which influence the learning of Social Science for getting the conclusion more easily.Â Based on the results of data analysis, it can be concluded that dehumanization on the teaching and learning process in MTs. Al-Azhar Tuwel was high enough. The influence of dehumanization factors on the teaching and learning process were teaching method for 77.9%, curriculum factor for 85%, teacher-student relationship for 63.7%, student-teacher relationship for 67.5%, school discipline for 75.4%, homework for 65.4%, school time for 63.7%, learning equipment for 70.8%, over-standard lesson for 81% and building condition for 80%. The most dominant factor which influenced the dehumanization of teaching and learning process is curriculum for 85%. Therefore; teachers need to improve their competences and capabilities to create the more humanist teaching learning process which is appropriate to the goals of education. For achieving the goals, it is recommended for the schools administrators to improve the facilities and infrastructure for getting the more conducive teaching learning process with the representative space and facilities.